(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the overall pathological morphology of brain contusions caused by road traffic accidents. Method: A Scoping review method was used in the study. The search strategy for scientific articles in PubMed and Google Scholar libraries. Full-text articles were searched and screened based on PRISMA-ScR guidelines, and 10 articles published between 2014 and 2024 were selected for synthesis. Results: Types of brain contusions include: primary lesions, secondary lesions, focal lesions, diffuse lesions, and symmetric lesions. The histopathological images of brain contusions are diverse: closed wall lesions after TTSN, open brain lesions after TTSN, meningeal lesions after TTSN, skin lesions of the head, and axonal lesions. Conclusion: For forensic doctors, in addition to recognizing gross lesions, it is necessary to know and understand microscopic lesions to have a comprehensive view of traumatic brain injury in general, brain contusion in particular, especially in assessing the time of injury.